2012
DOI: 10.1007/s12663-011-0321-y
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol Versus Ketorolac in the Treatment of Postoperative Pain Following Maxillofacial Surgery

Abstract: Pain plagues daily activity and hence its management would require alleviation at both the mental and physical planes, thus, bringing about comfort. It includes delivering analgesics in parenteral or oral form, or patches depending on the intensity and availability. Best analgesic regimens are ones that offer broad coverage, easy to administer, safe and economical. A drug seemingly appropriate to treat moderate to severe pain would be Tramadol hydrochloride, a centrally acting synthetic opioid analgesic with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
1
16
1
1
Order By: Relevance
“…Ketorolac has been a preferred due to its advantages over other NSAID’s. These include less likely alterations to the bleeding time, less likely to cause acute renal failure in patients with pre-existing renal impairment, less likely combination reactions when co-administered with other drugs and single dose administration [ 20 ]. Considering the advantages of ketorolac over other NSAID’s this systematic review and meta-analysis identified the anaesthetic efficacy of inferior alveolar nerve block after pre-medication with ketorolac.…”
Section: Discussionmentioning
confidence: 99%
“…Ketorolac has been a preferred due to its advantages over other NSAID’s. These include less likely alterations to the bleeding time, less likely to cause acute renal failure in patients with pre-existing renal impairment, less likely combination reactions when co-administered with other drugs and single dose administration [ 20 ]. Considering the advantages of ketorolac over other NSAID’s this systematic review and meta-analysis identified the anaesthetic efficacy of inferior alveolar nerve block after pre-medication with ketorolac.…”
Section: Discussionmentioning
confidence: 99%
“…Shankariah et al reported that the mean post-cesarean pain intensity was significantly lower in subjects who received ketorolac as an NSAID and tramadol as an opioid, compared to patients who received placebo. In addition, a more significant difference was observed between subjects who consumed tramadol and those who consumed ketorolac (23).…”
Section: Discussionmentioning
confidence: 87%
“…Elia (2005) argued that NSAIDs have a better effect on pain relief compared to opioids. Shankariah et al (2012) compared the effect of IM injection of Ketorolac and Tramadol, and found that both of these drugs reduced pain intensity from 2 to 24 hours postoperatively, but tramadol was always more effective in pain control compared to Ketorolac. Although ketorolac and methadone both reduce pain, we found in our study, Ketorolac reduced more pain as compared to methadone.…”
Section: Research Articlementioning
confidence: 99%